Rapamycin reduces severity of senile osteoporosis by activating osteocyte autophagy. Issue 3 (March 2016) - Luo, D.; Ren, H.; Li, T.; Lian, K.; Lin, D.
Abstract Summary Osteocyte is the orchestrator of bone remolding and decline in osteocyte autophagy is involved in senile osteoporosis. Our results suggested that rapamycin, at least in part by activating osteocyte autophagy, reduced the severity of age-related bone changes in trabecular bone of old male rats. Introduction Previous literatures have showed that osteocyte is the orchestrator of bone remolding and age-related decline in osteocyte number is associated with senile osteoporosis. Autophagy is an important cellular protective mechanism which can preserve osteocyte viability and failure of autophagy in osteocyte with age has been linked to senile osteoporosis. The purpose of this study was to explore whether rapamycin, one activator of autophagy, has protective effects on senile osteoporosis through inducing osteocyte autophagy. Methods Fifty-two 24-month-old male Sprague-Dawley (SD) rats were randomly divided into two groups. Rapamycin (1 mg/kg weight/day) or DMSO vehicle control was administered intraperitoneally for 12 weeks. BMD and bone microstructure were determined by Micro-CT. Fluorochrome labeling of the bones was performed to measure the mineral apposition rate (MAR). TRAP staining was performed to evaluate osteoclast number. The plasma levels of bone turnover markers were also analyzed. The effects of rapamycin on osteocyte autophagy were determined by immunohistochemistry, Western blot, and q-PCR. TUNEL was used to determine the prevalence of osteocyte apoptosis. Results Micro-CT evaluation demonstrated that rapamycin had a protective effect on age-related bone loss in trabecular bone. Besides, rapamycin resulted in an obvious increase of MAR and a decrease of osteoclast number in contrast to the control group. Furthermore, rapamycin also induced autophagy in osteocyte demonstrated by increased LC3-positive osteocyte and increased LC3 turnover. In addition, rats treated with rapamycin exhibited decreased apoptosis of osteocyte determined by TUNEL. Conclusions These results suggested that rapamycin, at least in part by activating osteocyte autophagy, reduced the severity of age-related bone changes in trabecular bone of old male rats. Therefore, rapamycin might be a feasible therapeutic approach for senile osteoporosis.